PENERAPAN TEKNOLOGI SEAMER KONTROL BERBASIS IOT SEBAGAI PENGONTROLAN KALENG SARDEN DI DESA LABUHAN TANGGA HILIR KABUPATEN ROKAN HILIR PROVINSI RIAU - Debi Setiawan; Ramalia Noratama Putri; Anna Anggraini (Jurnal Hilirisasi IPTEKS, 2023)
Geographically, Labuhan Tangga Hilir Village is located in the northernmost part of Riau Province, which is also the eastern coastal region of Sumatra Island. So that Labuhan Tangga Hilir Village has fisheries and marine resource potential. The potential for fisheries and marine resources consists of capture fisheries potential, cultivation and processing fisheries potential. The problem in the Labuhan Tangga Hilir Village area is that fishermen catch a lot and are abundant so they are not sold out, which causes the fish they catch to rot and have no economic value. The average catch of fishermen per month is 1.3 tons, with details of 500 kg being sold and 800 kg being wasted every month. The solution to this problem requires training in making sardines and the implementation of SIKOSA innovation technology tools based on the Internet of Things. The aim of the activity is to move the progress and welfare of the community to develop the natural resources they have, namely sea fish catches, increase income and manage good business. The activity methods used to solve partner problems are design, training, mentoring and implementation. The activity was held on Saturday 11 November at the Labuhan Tangga Hilir Pengalengan hall, Rokan Hilir Regency, Riau province. The activity was attended by approximately 20 participants. The results of the activity can increase knowledge of making sardine products and business opportunities for the people of Labuhan Tangga Hilir Village. The conclusion of this activity is that this training provides an increase in the community's knowledge about making sardines. So that it helps improve the economy of village communities, and has downstream products from fishing.